Art Therapy In Palliative Care: Cancer Patients (Journal of Pharmaceutical Negative Results, 2023)
In order to enhance the efficacy of art therapy sessions, this study looked at whether visual beauty and the joy that comes from creative endeavours might help alleviate symptoms experienced by palliative care patients. Method: Before and after a one-hour art therapy session, patients performed a self-assessment of six symptoms (pain, anxiety, illness, weariness, sorrow, and depression) that was modified from the Edmonton Symptom Assessment System (ESAS). After the session, a self-evaluation of aesthetic feeling was used to complete this assessment. Next, a correlation analysis was carried out. Our results support the efficacy of art therapy in easing pain in the palliative setting. We offer ideas as well for the future development and enhancement of these meetings.